Why architectural theory is not developing - Rappaport, Alexander (project baikal, 2022)
This article is devoted to the problem of architecture’s relative independence from its theory. From the 18th to the 20th century, architects followed scientists in inventing theories using numbers, formulas and figures. They tried to comprehend architecture with the help of space and time categories, applying biological and linguistic theories to architecture. The author states that the phenomenon of architectural theory can only be explained from the postulate of its independence as a form of human culture.